Density functional theory simulation of magnetism due to atomic vacancies in graphene using siesta - Jarkoni, Norshila (2013)
Spintronics generally refers to technology where devices utilise the spin of the electron in addition to its charge for information transmission, processing and storage.Graphene is a sheet of carbon atoms bound together with double bonds (called the sp2bonds) in a thin, one atom thick layer. It is a very special material because of the large spin relaxation length and ballistic transport characteristics that can provide a great platform for developing spin-polarized devices. The carbon atom itself does not own any magnetic moment, therefore, the researches on graphene-based spintronics mainly focus on the substantial magnetism in graphene due to the presence of defects. This study will investigate the magnetism originating from quasilocalised states inducedby defects in graphene sheet using first principle approach. The density functional theory calculations were performed using SIESTA software in the spin-unrestrictedmanner, using the diagonalization-based method for solving Kohn-Sham equations.The calculation was done in parallel modes. The generalized gradient approximation(GGA) exchange-correlation functional of Perdew, Burke and Ernzerhof (PBE) was used throughout this work. In addition, all the calculations for the models were carried out using the double-zeta plus one polarization (DZP) basis set. In this study, the magnetic moments generated due to atomic vacancies were calculated for supercellsof different sizes namely 3×3, 4×4, 5×5, and 6×6 multiples of the graphene unitcell.The results show that the values of the magnetic moment in graphene supercell sstrongly depend on the size of the supercell, the number of the vacancies as well as on the sublattice where the vacancies are located. This is generally consistent with Lieb’stheorem regarding the magnetism in materials with different sublattices. Furthermore the presence of exchange splitting in the density of states (DOS) for electrons with different spins can be considered as indication that this magnetism is of the itinerant type and this should enhance the potential of using graphene for spintronic devices.